1975
DOI: 10.1104/pp.56.1.126
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Isotope Fractionation during Photosynthesis in a Blue-Green and a Green Alga

Abstract: Oxygen isotope fractionation (180/160) at the natural abundance level has been measured during photosynthesis of a blue-green and a green alga. When sufficient attention is paid to removal of contaminating air 02 before and during the experiments, then the photosynthetic 02 evolved, as compared to the water 02, had an average difference of -0.36%0 for a blue-green alga and -0.80%0 for a green alga. MATERIALS AND METHODSThe blue-green alga, Agmenellum quadruplicatum, strain PR-6, was grown in modified ASP-2 (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 5 publications
3
37
0
Order By: Relevance
“…Aerobic respiration across a range of organisms has been found to exhibit a  of 0.518 . We followed previous workers (e.g., Luz and Barkan, 2005) Stevens et al, 1975;Guy et al, 1987;Guy et al, 1993;Helman et al, 2005;Eisenstadt et al, 2010). Measureable isotopic fractionations have been observed for some algae in which the  18 O value of newly photosynthesized O 2 is up to 7‰ higher than of the source H 2 O; this has been attributed to an unknown reductive process hypothesized to occur in algal cells after O 2 formation (Eisenstadt et al, 2010).…”
Section: Background On the Isotopic Composition And Biogeochemistry Omentioning
confidence: 96%
“…Aerobic respiration across a range of organisms has been found to exhibit a  of 0.518 . We followed previous workers (e.g., Luz and Barkan, 2005) Stevens et al, 1975;Guy et al, 1987;Guy et al, 1993;Helman et al, 2005;Eisenstadt et al, 2010). Measureable isotopic fractionations have been observed for some algae in which the  18 O value of newly photosynthesized O 2 is up to 7‰ higher than of the source H 2 O; this has been attributed to an unknown reductive process hypothesized to occur in algal cells after O 2 formation (Eisenstadt et al, 2010).…”
Section: Background On the Isotopic Composition And Biogeochemistry Omentioning
confidence: 96%
“…However, Metzner (1978) suggested that instead hydrogen carbonate (bicarbonate; HCO − 3 ) is the immediate substrate for O 2 formation that is subsequently replenished by the reaction of CO 2 with H 2 O. This hypothesis was discounted for long because the isotopic equilibration between 18 O-water and HCO − 3 is too slow to account for early isotope labeling studies (Ruben et al, 1941; Stemler and Radmer, 1975; Stevens et al, 1975; Radmer and Ollinger, 1980). Due to the discovery that a carbonic anhydrase (CA) activity is associated with PSII (Lu and Stemler, 2002; Villarejo et al, 2002; Moskvin et al, 2004) the “bicarbonate-as-substrate hypothesis” needed to be re-investigated with refined expriments.…”
Section: Is Water the Immediate Substrate Of Photosynthetic O2 Evolutmentioning
confidence: 99%
“…Previous investigators used whole cells or leaves (Dole and Jenks, 1944;Vinogradov et al, 1969;Stevens et al, 1975;Metzner et al, 1979); consequently, there was potential for simultaneous 0 2 uptake by the competing processes of respiration, photorespiration, and the Mehler reaction. Results of some of these studies were superficially consistent with a reverse isotope effect favoring the production of isotopically heavy 02.…”
Section: O2 Evolutionmentioning
confidence: 99%
“…It is interesting to note that Metzner et al (1979) observed the greatest apparent fractionation of photosyn- 01,1993 thetic O2 (+15%0) under aerobic conditions known to favor photorespiration (Canvin et al, 1980). Stevens et al (1975) examined photosynthetic O2 accumulated by cultures of a cyanobacterium and a green alga at DIC concentrations high enough to keep the rate of photorespiration negligible. The difference in 6I8O between the source water and the collected O2 was near zero, indicating that there could not be a reverse isotope effect in the photolysis of water.…”
Section: O2 Evolutionmentioning
confidence: 99%